An Anodic Phase Can Facilitate Rather Than Weaken a Cathodic Phase to Activate Neurons in Biphasic-Pulse Axonal Stimulations - Zheng, Lvpiao; Feng, Zhouyan; Xu, Yipeng; Yuan, Yue; Hu, Yifan (Frontiers in Neuroscience, 2022)
Electrical pulses have been utilized in neural stimulations to treat various diseases promisingly. Usually, charge-balanced biphasic-pulses are applied in clinic to eliminate the possible side effects caused by charge accumulations. Because of its reversal action to the preceding cathodic-phase, the subsequent anodic-phase has been commonly considered to lower the activation efficiency of biphasic-pulses. However, an anodic-pulse itself can also activate axons with its “virtual cathode” effect. Therefore, we hypothesized that the anodic-phase of a biphasic pulse could facilitate neuronal activation in some circumstances. To verify the hypothesis, we compared the activation efficiencies of cathodic-pulse, biphasic-pulse and anodic-pulse applied in both monopolar and bipolar modes in the axonal stimulation of alveus in rat hippocampal CA1 region in vivo. The antidromically-evoked population spikes (APS) were recorded and used to evaluate the amount of integrated firing of pyramidal neurons induced by the pulse stimulations. We also used a computational model to investigate the pulse effects on axons at various distances from the stimulation electrode. The experimental results showed that with a small pulse intensity, a cathodic-pulse recruited more neurons to fire than a biphasic-pulse. However, the situation was reversed with an increased pulse intensity. In addition, setting an inter-phase-gap of 100 μs was able to increase the activation efficiency of a biphasic-pulse to exceed a cathodic-pulse even with a relatively small pulse intensity. Furthermore, the latency of APS evoked by a cathodic-pulse was always longer than that of APS evoked by a biphasic-pulse, indicating different initial sites of the neuronal firing evoked by the different types of pulses. The computational results of axon modeling showed that the subsequent anodic-phase was able to relieve the hyperpolarization block in the flanking regions generated by the preceding cathodic-phase, thereby increasing rather than decreasing the activation efficiency of a biphasic-pulse with a relatively great intensity. These results of both rat experiments and computational modeling firstly reveal a facilitation rather than an attenuation effect of the anodic-phase on biphasic-pulse stimulations, which provides important information for designing electrical stimulations for neural therapies.